Small Hepatocellular Carcinoma With Low Tumor Marker Expression Benefits More From Anatomical Resection Than Tumors With Aggressive Biology. Issue 3 (March 2019) - Jung, Dong-Hwan; Hwang, Shin; Lee, Young-Joo; Kim, Ki-Hun; Song, Gi-Won; Ahn, Chul-Soo; Moon, Deok-Bog; Lee, Sung-Gyu
Abstract : Objective: We assessed prognostic advantage of anatomical resection (AR) over nonanatomical resection (NAR) for hepatocellular carcinoma (HCC) according to multiplication of α-fetoprotein, des-γ-carboxyprothrombin, and tumor volume (ADV) scores. Background: Superiority of AR over NAR is debated. ADV score is surrogate marker of postresection prognosis for solitary HCC. Methods: This study included 1572 patients who underwent curative resection for solitary HCC of 2.0 to 5.0 cm between 2006 and 2014. Results: Preoperative patient profiles were not statistically different between AR and NAR groups. In 1324 naïve patients without preoperative treatment, AR group showed lower recurrence rates ( P = 0.003) and higher patient survival rates ( P = 0.012) than NAR group. AR group showed lower recurrence rates in patients with ADV ⩽5 log ( P  ⩽ 0.046). ADV scores >4 log and >3 log were independent risk factors for tumor recurrence and patient survival in treatment-naïve patients, respectively. In treatment-naïve group with preserved hepatic functional reserve, AR group showed lower recurrence rates in patients with ADV ⩽4 log ( P = 0.026). Absence of microvascular invasion also showed lower recurrence rates ( P = 0.007) in AR group. In 248 patients with preoperative treatment, AR group showed lower recurrence rates ( P = 0.001) and higher patient survival rates ( P = 0.006). AR group showed lower recurrence rates in patients with ADV ⩽4 log ( P < 0.001) and higher survival rates in patients with ADV ⩽5 log ( P  ⩽ 0.043). Conclusions: Prognostic benefit of AR was evident in patients with ADV score ⩽4 log or absence of microvascular invasion. Patients with less aggressive tumor biology benefit more from AR than NAR, thus being reasonably indicated for AR. Abstract : Supplemental Digital Content is available in the text